Development of Semi-Interface Motorcycle Simulator (SiMS) - Muhammad Syahmi Wan Fauzi, Wan; Rahman Omar, Abdul; Rashid, Helmi (International Journal of Engineering and Technology, 2018)
Recently, studies concerning motorcycle have been an overwhelming area of research interest. As an alternative to the real world assessment, researchers have utilized motorcycle simulator as a workstation to conduct studies in the motorcycle niche area. This paper deal with the development of a new motorcycle simulator named Semi-Interface Motorcycle Simulator (SiMS). Combination of Computer Aided Design (CAD) and Finite Element Analysis (FEA) software made it possible to design and simulates the motorcycle simulatorâ€™s conceptual design before being fabricated. The SiMS setup not only provides a near-to-real and immerse motorcycle riding experience on a super sport motorcycle model, but it also allows safer high speed motorcycle simulations to be conducted in a controlled environment that is portable and ergonomically easier to transport to various venues.Â Â